Promosi Makanan Khas Indonesia Melalui Wirausaha Jasa Berbasis Website Indonesia-Food.com - Fela, Randy Frans; Zharif, Luthfi; Arifani, Erlina Nur; Friansyah, Rizal; Syifaurrohmah, Mulia Ela (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
Indonesian culinary diversity is a Godâs grace for Indonesia to develop its culture in the eyes of the world. Unfortunately,itâs not recognized massively in the world. Regarding to this problem Indonesian-Food.com was born to expose Indonesian culinary to the world. Indonesian-Food.com is a business promotion services that uses websites Indonesia-Food.com. This website uses WordPress Content Management System and Business Finder wordpress theme. The website features included culinary map, search engines, as well as a minimalist user interface. To expand the business, promoting with offline and online media, and promoting the Indonesian-Food.com website while searching partnership. Offline media used includespartnership proposals, leaflets, and merchandises while online media relies on Indonesian-Food.com websites and social networks such as Facebook, Twitter, and Google Plus. Indonesian business-Food.com managed to hook 15 partners with an income of Rp. 2,800,000.00. Break Event Point can be reachedafter gaining 19 partners within 6 months, which equivalent to Rp. 3,654,000.00. Keywords : Indonesian culinary, promotion, Indonesian-Food.com